2006
DOI: 10.1192/apt.12.2.81
|View full text |Cite
|
Sign up to set email alerts
|

Assessing professional and clinical competence: the way forward

Abstract: Recent developments in postgraduate medical education for the training of junior doctors in the UK necessitate changes in all parts of the curriculum, including the assessment system. There is a move away from the limited, traditional one-off assessment towards multidimensional, broader assessments of a doctor's longer-term performance. This is accompanied by the rapid development of assessment tools, collectively termed workplace-based assessments, and is in keeping with an outcome-based approach to medical e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…Also portfolio is often used to assess professional development (Michels, 2009). CSR is to evaluate the trainee's clinical decision-making, reasoning and application of medical knowledge with real patients and DOPS is appropriate for competencies patient care, professionalism, interpersonal skills, communication (Gigante & Swan, 2010) and anywhere practical skills are important (Brown & Doshi, 2006). The results of this study showed that Mini-CEX is the most suitable and the most feasible assessment tool for competencies "Interviewing" and "Develop & Carry out pt.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…Also portfolio is often used to assess professional development (Michels, 2009). CSR is to evaluate the trainee's clinical decision-making, reasoning and application of medical knowledge with real patients and DOPS is appropriate for competencies patient care, professionalism, interpersonal skills, communication (Gigante & Swan, 2010) and anywhere practical skills are important (Brown & Doshi, 2006). The results of this study showed that Mini-CEX is the most suitable and the most feasible assessment tool for competencies "Interviewing" and "Develop & Carry out pt.…”
Section: Discussionmentioning
confidence: 82%
“…A multi-method assessment might include direct observation of the student interacting with several patients at different points during the rotation, a multiple-choice examination with both "key features" and "script-concordance" items to assess clinical reasoning, an encounter with a standardized patient followed by an oral examination to assess clinical skills in a standardized setting, written essays that would require literature searches and synthesis of the medical literature on the basic science or clinical aspects of one or more of the diseases the student encountered, and peer assessments to provide insights into interpersonal skills and work habits (Ronald & Epstein, 2007). Clearly, no single rating is able to provide the whole story about any doctor's ability to practice medicine, as this requires the demonstration of ongoing competence across a number of different general and specific areas (Brown & Doshi, 2006). Multiple assessment methods and multiple perspectives, however, provide rich data that support a resident's ability (or inability) to perform as a medical practitioner upon graduation and finally assessment results provide feedback to both the resident and faculty that the resident is making expected progress in achieving the knowledge, skills, and attitudes outlined by the objectives (Joyce, 2006).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations